O reconhecimento e a execução de sentenças arbitrais estrangeiras no Brasil: atualizado com o novo CPC - Law, Thomas (2016)
This Master s Thesis focuses on the acknowledgement and enforcement of foreign arbitral awards in Brazil, based on the theoretical and practical research in the fields of civil procedural law and international law, considering it includes a study on the different international laws, conventions and treaties on international commercial arbitration, as well as on the acknowledgement and enforcement of arbitral awards. The first part of the study refers to the events of direct enforcement and nationalization of foreign arbitral awards, according to the new legal provisions of the New Brazilian Code of Civil Procedure. The second part of the study covers the assessment of the ratification process of foreign arbitral awards before the Superior Court of Justice (STJ), considering Brazil s new Code of Civil Procedure, the new internal rules of the Superior Court of Justice, the Arbitration Law and the New York Convention. The thesis also covers two cases, specifically, judged by the Superior Court of Justice: SEC No. 2,410 (Ferrocarriles versus Supervia Concessionária de Transportes Ferroviário S/A) and SEC No. 826 (Ssangyong Corporation versus Eldorado Indústrias Plásticas Ltda). Finally, after the reflection on the research conducted, one argues nationalization of the foreign arbitral award is possible given the new provisions included in Brazil s new Code of Civil Procedure and the acknowledgement thereof by the Superior Court of Justice, in the possibility of nationalization of the arbitral award in the Appeal to the Superior Court of Justice No. 1.231.554